Thermal diffusion effect analysis of micropolar nanofluid flowing on inclined surface: a chemical engineering case study - Shankar Goud, B.; Jamshed, Wasim; Ahmad, Hijaz; Safdar, Rabia; Mohamed Isa, Siti Suzilliana Putri; Hussain, Syed M.; Bayram, Mustafa; Dharmaiah, G. (John Wiley and Sons, 2025)
This investigation was carried out to study the microrotational flow of nanoliquids across an extensible surface. The dispersion of nanomaterials in everyday liquids is becoming a major focus of nanotechnology. Dispersing nanoparticles in a conventional liquid increases its thermal conductivity, which is useful for both generating and transferring energy. The primary focus of this study has been on energy transportation. Thermal radiations and Soret implications were used in this investigation. The Soret impacts are also taken into account. Here, the numerical research is based on the Buongiorno model. Using suitable similarity conversions, the flow mathematical equations are converted into the nonlinear ordinary differential equations. This study makes use of the popular numerical bvp4c method. Graphs and tables are used to illustrate the physical quantities, which include a number of impacts that are caused by the constraints of the component. The key findings are that high magnetic field factor, thermophoresis factor, Brownian motion factor, and radiation factor cause high-temperature distribution. Moreover, thermophoresis and Brownian motion factors are responsible for enhancing the variation of Nusselt and Sherwood numbers. The growth in Nusselt number is controlled by the material factor, Lewis number, radiation factor, Soret number, and inclination angle. The presence of thermophoresis parameter, radiation factor, and inclination angle generate growth in Sherwood number.